COVID-19 medidas preventivas: Como prepararse contra un brote en su comunidad - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS)
These flyers, written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NC State University Extension), provide quick, digestible information regarding prevention of COVID-19 and procedures for food service, grocery stores, and other food-related businesses. This flyer in particular is the Spanish translation of FSHN20-4/FS327: COVID-19 Preventative Measures: Preparing for an Outbreak in Your Community. Published by the UF/IFAS Food Science and Human Nutrition Department, March 2020.